(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
Wattakaka volubilis (Linn) is used as a phytomedicine for liver diseases. In the present study the effect of methanolic extract of Wattakaka volubilis powder was carried out against the Aluminium toxicity in rat model. Various doses of Wattakaka volubilis extract (100, 200, 400 mg/kg/b.w) was given orally for 30 days to Aluminum sulphate toxicity exposed rats. They were observed each hour for 24 h and each day for 30 days for any changes in behavioural activity and mortality. Clinical observation, body weight, organ weight, biochemical enzymatic analysis and histological examination were carried out. The extract was found to possess hepatoprotective activity in a dose dependent manner and the effect was comparable with silymarin, a standard drug. The extract significantly reduce the toxicity of Aluminium sulphate caused in liver due to the presence of phytoconstituents such as alkaloids, sterols, tannins, triterpenoids and flavonoids which are known hepatoprotectant.